No-Carrier-Added [18F]Fluorobenzene Derivatives as Intermediates for Built-up Radiosyntheses - Ermert, Johannes; H. Coenen, Heinz (Current Radiopharmaceuticals, 2010)
This review summarizes the possibilities of built-up syntheses of no-carrier-added radiofluorinated aromatic tracers via [18F]fluorobenzene derivatives as intermediate compounds.
Keywords: Fluorine-18